2017
DOI: 10.1177/1532708617706117
|View full text |Cite
|
Sign up to set email alerts
|

Neoliberalism in Higher Education: Can We Understand? Can We Resist and Survive? Can We Become Without Neoliberalism?

Abstract: Concern regarding capitalism, profiteering, and the corporatization of higher education is not new. A market focus that creates students as consumers and faculty as service providers has dominated global practices in colleges and universities for some time. Most recently, however, this more liberal market-driven focus has actually morphed away from a jurisdictional emphasis (with a potential focus on fairness) to forms of veridiction (neoliberal truth regimes) that legitimate intervention into all aspects of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 13 publications
0
46
0
Order By: Relevance
“…However, experienced stress has a great effect on students' experiences of the workload involved with their main subject. To counter and eliminate the negative impact of neoliberalism on students' well-being whilst studying, there is an urgent need for interventions which utilise research on music students' health (Ginsborg et al 2009;Williamon and Thompson 2006) in connection with possible alternative courses of action, such as changing competition within an institution to co-operation (Fernández-Herrería and Martínez-Rodríguez 2016; Fitzpatrick 2019) and revising the purposes and contents of study programmes with reference to diverse sources of knowledge (Cannella and Koro-Ljungberg 2017). In this study, we listened to music students' experiences and showed how their valuable voices can contribute to a wide spectrum of knowledge, and become a form of research-based evidence which could potentially be utilised in furthering both the development of university cultures and educational policies.…”
Section: Discussionmentioning
confidence: 99%
“…However, experienced stress has a great effect on students' experiences of the workload involved with their main subject. To counter and eliminate the negative impact of neoliberalism on students' well-being whilst studying, there is an urgent need for interventions which utilise research on music students' health (Ginsborg et al 2009;Williamon and Thompson 2006) in connection with possible alternative courses of action, such as changing competition within an institution to co-operation (Fernández-Herrería and Martínez-Rodríguez 2016; Fitzpatrick 2019) and revising the purposes and contents of study programmes with reference to diverse sources of knowledge (Cannella and Koro-Ljungberg 2017). In this study, we listened to music students' experiences and showed how their valuable voices can contribute to a wide spectrum of knowledge, and become a form of research-based evidence which could potentially be utilised in furthering both the development of university cultures and educational policies.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the nature and time needed to build relationships with First Nations Peoples are seemingly not well understood or facilitated within the dominant research culture. At times, the language used in dominant research spaces has seemingly constructed relationships as commodities for research output, which risks paradoxically exhausting those relationships with Indigenous peoples to benefit one's self or the institution (Ball, 2012;Cannella and Koro-Ljungberg, 2017). To elaborate, during the PhD candidature, there are multiple meetings held to track and oversee my 'progress'.…”
Section: Paradoxes In Decolonising Research Approachesmentioning
confidence: 99%
“…The key aspects of neoliberalism are value-for-money, the rise of managerialism, consumerism, accountability and strictly controlled performance audit culture. In the university – as in other institutions – neoliberal governance aims to create and protect competition as the organizing principle for societal decision-making (Canella and Koro-Ljungberg, 2017: 156). Competition as a guiding rationale is individualizing: it leaves little room for solidarity or academic staff as a collective.…”
Section: Neoliberalization and Marketization Of The University: An Ovmentioning
confidence: 99%